Stability Constants of 2N-(3,5-Diiodo Salicylidene)-5-Phenyl 1,3,4-Thiadiazole Complexes with Cu2+, Ni2+ and Fe3+. - GUPTA, M.L. (Asian Journal of Chemistry, 2010)
In the present communication the stability constants of 2N-(3,5-diiodo salicylidene)-5-phenyl 1,3,4-thiadiazole complexes with Cu2+, Ni2+ and Fe3+ are reported.